1921 February rebellion as a manifestation of Armenian war of independence - Stepanyan, Khachatur (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2021)
Georgia, Azerbaijan and Armenia declared their independence in the spring of 1918. After the signing of the Armistice of Compiègne and the annulment of the Treaty of Brest-Litovsk that had been agreed upon between Soviet Russia and the Central Powers, the Soviet Red Army started a campaign to capture the areas that had belonged to Russia. Armenia had to fight two enemies – the Turkey of Mustafa Kemal Atatürk on the one side and Soviet Russia on the other. Turkey attacked Armenia in the autumn of 1920. Even though Soviet Russia had signed a treaty with Armenia in August, the Armenian Bolsheviks, supported by the Red Army, proclaimed the Soviet Republic of Armenia in November and began Sovietization of the country, accompanied by repressions against Armenian national politicians, military leaders and intellectuals. As a result of an uprising that began in February 1921, the Bolsheviks were ousted from Yerevan, the capital of Armenia, but the counter-offensive of the Red Army in April restored the Bolshevik rule in Armenia.